Comunicación intrafamiliar y su influencia en el consumo de sustancias de un adolescente - Gomez Ramos, Marcela Andreina (2020)
The purpose of this case study is to analyze the influence of intrafamily communication and its responsibility in the consumption of substances by a 15-year-old teenager from the 10 de Agosto School of the Montalvo Canton Province of Los Ríos. Where a verbal exchange was carried out through the technique as an interview, in addition to obtaining the necessary information, it was collected through the techniques of clinical history, observation guidance, and the application of Hamilton's anxiety test of 14 items, designed to evaluate the severity of a patient's anxiety and the Hamilton depression test used in patients previously diagnosed with depression; giving as results that there is no good communication or relationship between the mother and daughter, which is assumed that this is the first cause for the daughter to think that no one in the family loves her so she stays away from them.